Pengaruh Celebrity Endorser dan Harga Terhadap Minat Beli Konsumen Pada Produk Scarlett Whitening Melalui Sosial Media Instagram - Septiani, Karimah; Desfitriady, Desfitriady (Rifa'Institute, 2023)
In the midst of very intense competition, companies must be more selective in setting prices for a product, because in general branding and price are measuring factors for consumers in purchasing a product. This research was conducted on students of the Faculty of Economics Regular Evening at Pasim National University who bought scarlett whitening. The purpose of this study was to find out how much influence the influence of celebrity endorsers and prices have on buying interest either partially or simultaneously through Instagram social media. The research method that will be used in this research is descriptive method and associative method. In this study, the unit of analysis was the individual, namely students of the Faculty of Economics, Evening Regular Class, Pasim National University who bought scarlett whitening products. The sample in this study were 97 respondents. Accidental sampling is the sampling technique used in this study. The analytical method uses multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study, it shows that there is a partial or simultaneous influence on the Celebrity Endorser variable with a contribution value of 39.8% to consumer buying interest and 10.2% contributing to the effect of price on consumer buying interest. And the influence of Celebrity Endorser and Price partially or simultaneously contributes to purchase intention by 50% while the remaining 50% is the influence of other variables not examined.